Reshaping the World : Debates on Mesoamerican Cosmologies - Díaz Álvarez, Ana María (Book collections on Project MUSE., 2020)
"An exploration of the plurality, complexity, and adaptability of Precolumbian and colonial-era Mesoamerican cosmological models and the ways anthropologists and historians have used colonial and indigenous texts to understand these models. That model comprised nine fixed layers of underworld and thirteen fixed layers of heavens"--